Severity and Endurance in Eating Disorders: An Exploration of a Clinical Sample From Chile - Dapelo, Marcela M.; Gil, Aurora A.; Lacalle, Lucas; Vogel, Melina (Frontiers in Psychiatry, 2020)
Introduction One in five patients with eating disorders (EDs) may take a lasting course. It has been proposed that this enduring group exhibits increased severity, such as low treatment response, severe symptomatology, and poor quality of life. However, there is no consensus defining this group. Moreover, most of the literature comes from high-income societies and may not apply to developing countries. Aims This study aimed to evaluate the association between endurance (length of ED) and severity (previous treatments, hospitalizations, medical complications, symptomatology and clinical impairment) in individuals with EDs from Chile. In addition, it aimed to explore the association between endurance and delays seeking specialized treatment. Methods Forty-one women with EDs (16 with anorexia nervosa, 11 with bulimia nervosa, 10 with binge eating disorder and 4 with other specified EDs) completed a social-demographic survey, the Eating Disorders Examination Questionnaire, and the Clinical Impairment Assessment. Also, Body Mass Index, length of ED, and complications were retrieved from participants’ medical records. Spearman correlation coefficient and linear regression were used to explore the association between length of ED and measures of severity and treatment seeking behavior. Results There was no significant association between endurance (length of ED) and measures of severity. There was a significant association between length of ED and delays seeking specialized treatment (rs=0.72; p<0.01). Regression indicated that for each month in delay visiting a specialized ED treatment team, the ED duration increased by 0.87 months (F(1,38)=75.93; p<0.01; R2= 0.66). Discussion The findings suggest that in developing countries, where specialized treatment access is not widespread, defining SEED solely by the length of illness may not be clinically significant, and other criteria (e.g., timely access to evidence-based treatments) should be considered.